Análise do problema de máxima geração distribuída observando o critério estático da estabilidade de tensão - Abreu, Isabela Fernanda Natal Batista (2017)
The Distributed Generation (DG) growth in Brazil and worldwide is followed by many advantages, disadvantages and uncertainties about the system behavior regarding some criteria such as reliability, availability and voltage stability. As new DG players request their connection in the distribution network, a comprehensive analysis must be performed, in order to better assess their impact in the network. This work formulates the Maximum Hosting Capacity (MHC) as an optimization problem built upon the classical Optimal Power Flow (OPF), solved by an Interior-Point Method combined with Scatter Search Metaheuristics. The MHC problem, invariably constrained either by overvoltages or overcurrents, may yield a solution that can lie in the bottom part of the classical PV curve in static voltage stability analysis. If this is the case, there is a need to reformulate the optimization problem including a new constraint to enforce solutions only on the upper part of the PV curve.